2019
DOI: 10.3389/fpsyg.2019.02433
|View full text |Cite
|
Sign up to set email alerts
|

ORCA.IT: A New Web-Based Tool for Assessing Online Reading, Search and Comprehension Abilities in Students Reveals Effects of Gender, School Type and Reading Ability

Abstract: ORCA.IT, a new online test of online research and comprehension was developed for the Italian population. A group of 183 students attending various types of upper secondary schools in Northern Italy were tested with the new tool and underwent further cognitive and neuropsychological assessment. The different school types involved in the study are representative of the school population in the Italian system, but can also be easily compared with the educational systems of other countries. The new test turned ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 73 publications
2
8
1
1
Order By: Relevance
“…This result replicates well‐known effects of verbal ability and skills (measured as Vocabulary, in this case) in digital text comprehension (Caccia et al, 2019; Hahnel et al, 2016; OECD, 2011; Salmerón, García, & Vidal‐Abarca, 2018). The expository materials in this study were of low previous knowledge for the students, but the texts were adapted from Wikipedia (e.g., not a specialized source), and their calculated reading level was ‘somewhat difficult’ and ‘pre‐university level’.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This result replicates well‐known effects of verbal ability and skills (measured as Vocabulary, in this case) in digital text comprehension (Caccia et al, 2019; Hahnel et al, 2016; OECD, 2011; Salmerón, García, & Vidal‐Abarca, 2018). The expository materials in this study were of low previous knowledge for the students, but the texts were adapted from Wikipedia (e.g., not a specialized source), and their calculated reading level was ‘somewhat difficult’ and ‘pre‐university level’.…”
Section: Discussionsupporting
confidence: 84%
“…For example, in the large multinational PISA study, the overall correlation between digital and print reading performance was 0.83 (OECD, 2011). Basic reading and verbal abilities, such as word knowledge, have also been associated with digital comprehension tasks (Blom et al, 2018; Caccia et al, 2019). This is an established finding in traditional reading comprehension (Nation, 2009; Perfetti, 2007), because word knowledge reflects not only decoding but lexical and semantic verbal abilities (Carroll, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…However, boys exhibit a longer gaze and focus on the current target. However, Caccia et al ( 2019 ) found a contradictory result, wherein boys scored higher than girls. They noted that this was because boys were better at spatial–visual tasks than at comprehension (Caccia et al, 2019 ).…”
Section: Discussionmentioning
confidence: 98%
“…However, Caccia et al ( 2019 ) found a contradictory result, wherein boys scored higher than girls. They noted that this was because boys were better at spatial–visual tasks than at comprehension (Caccia et al, 2019 ). This result is consistent with those of Benmarrakchi et al ( 2017 ), who addressed the role of information and communication technology (ICT) in supporting dyslexic students.…”
Section: Discussionmentioning
confidence: 98%
“…To select the appropriate patients for telerehabilitation, some feasibility criteria were followed: neuropsychological criteria, attentional, adaptive, and motivational requirements of children as well as network requirements such as connection stability, availability of devices in the family, and the children's and their families' familiarity and autonomy with new technologies. In this regard, the level of competence of children with LDs should not be overestimated, as recent studies have shown that, contrary to expectations, Italian students show little competence in the use of ICT [30].…”
Section: Introductionmentioning
confidence: 84%